United Kingdom : Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This report assesses fiscal transparency practices in the United Kingdom in relation to the requirements of the IMF's new Fiscal Transparency Code (FTC). Across all pillars evaluated in the code, the United Kingdom scores very highly when compared with other countries that have undergone an assessment. Of the 48 principles in the FTC, the United Kingdom meets 9 principles at the basic level, 10 principles at the good level, and 23 principles at the advanced level. Fiscal transparency practices are strongest in the area of fiscal reporting and resource revenue management. In four principles, the United Kingdom's transparency practices do not currently meet basic practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet